UJI BEBERAPA FORMULA INOKULUM TERHADAP PRODUKSI TUBUH BUAH JAMUR TIRAM PUTIH (Pleurotus ostreatus (Jacq.) P.Kummer.) - Dana Sulistia; Umrah Umrah; I Nengah Suwastika (Biocelebes, 2020)
The study of test for several inoculum formulas on the production of white oyster mushroom body (Pleurotus ostreatus (Jacq.) P.Kummer.) conducted from April to September 2018 at Biotechnology laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Tadulako University. This study were aimed to determine whether the treatment of the inoculum formula tested on the production medium can form the white oyster mushroom fruit body and to find out which inoculum formula can form the optimum fruit body in the production medium. This study was conducted by Randomized Complete Design (RAL) consisted of 4 treatments and four replications, I1 (100% corn seeds), I2 (50% : 23%: 27%), I3 (50% : 17% : 33%) dan I4 (95% : 5%). The results showed that I 3 was the best inoculum for the growth of the white oyster mushroom fruit body compared to the other inoculums which were characterized by a wide mushroom hood, the length was long and the weight of fresh mushroom was high. The inoculum formula and the best dosage for body production of white oyster mushroom are found in treatment I3 (50% sawdust + 17% corn flour + 33% bran).